DAMPAK KEBIJAKAN PEMBANGUNAN SMELTER TERHADAP EKSISTENSI DAN PENDAPATAN TENAGA KERJA LOKAL PERTAMBANGAN DI KABUPATEN KONAWE SELATAN - Irfan Ido (Universitas Halu Oleo, 2018)
This study aims to find out: the existence, income, and income of the local workforce of PT. Putra Intisultra Perkasa before and after the enactment of the smelter development policy. This research was conducted in Konawe Selatan District. The study was conducted by the 27 families who were a local workforce of PT. Putra Intisultra Perkasa. The analysis used is the Paired Sample Test t-test analysis and descriptive analysis.The results of this study indicate that: The existence of a local workforce PT. Putra Intisultra Perkasa after the enactment of the smelter development policy requires local workers to survive and find work after losing their profession, known to the average local worker PT. The son of Intisultra after the layoffs worked as a traditional rock miner in C and continued to work in the mining sector instead of returning to work in the agricultural sector. The income generated by the respondents of the local workforce PT. Putra Intisultra Perkasa before the enactment of the smelter development policy averaged Rp. 1,851,000 / month, revenue after the enactment of the smelter development policy, which averaged 1,525,773 (Rupiah / Month). There is a significant difference between the income of the local workforce of PT. Putra Intisultra Perkasa, before and after the enactment of the smelter development policy.